The influence of different negative feedback on the decay of self-deception - Liu, Juan; Ding, Wenjun; Deng, Liying; Tan, Min; Guan, Peipei (Frontiers in Psychology, 2025)
IntroductionThough some studies have found the positive influences of moderate self-deception on individuals and society, there are many that have shown its negative influences on individuals and society. Long-term self-deception will have negative influences which could cause high individual losses and even social disasters. Therefore, it is essential to abate the decay of self-deception to avoid its negative influences and help individuals to better monitor themselves.MethodsIn this research, we explored the impact of various types of negative feedback on the decay of self-deception using a forward-looking paradigm with three conditions: no-feedback, ambiguous negative feedback, and real negative feedback. The experiment under each condition was tested four times. The negative feedback was provided after Tests 2 and 3.ResultsThe results indicated that, in Test 1 of both Experiments 1 and 2, the answer group demonstrated notably stronger positive beliefs and a higher propensity for cheating compared to the control group. Additionally, self-deception was more pronounced under the no-feedback than under the negative feedback in the subsequent three tests. Furthermore, the condition of ambiguous negative feedback led to greater self-deception in the final three tests compared to the condition of real negative feedback in Experiment 2. The results also revealed that self-deception gradually diminished with real feedback in the answer group.DiscussionThe findings showed that both ambiguous and real negative feedback reduce self-deception, although real negative feedback having a greater effect than ambiguous feedback. Additionally, the reduction of self-deception was fundamentally related to a decrease in unrealistic positive beliefs, and this decline in self-deception was also influenced by monetary rewards.